Traditional Cultural Expressions and Intellectual Property Rights in Indonesia - Diah Imaningrum Susanti; Rini Susrijani; Raymundus I Made Sudhiarsa (Yuridika, 2019)
Protection of traditional culture and knowledge has been a concern in Indonesia. Efforts that have been made to legally protect Indonesian traditional expressions and knowledge usually involve intellectual property (IP) laws. However, the protection provided by IP laws may be inadequate for Indonesian traditional communities that care more about the survival and maintenance of their culture and knowledge than the legal exclusivity of their works. This study uses a normative legal approach with the perspective of hermeneutic circle to look at various studies and legal documents to find reasons why IP laws may not be entirely suitable for the Indonesian context and how an IP-based law can be designed to suit the actual needs of Indonesian traditional expression holders. The results obtained affirm that Indonesian traditional cultural expressions cannot be contained by laws that exclusively limit the usage of those expressions and thus a ‘sui generis’ law is needed to give a more appropriate protection.